Development Of Fuel Consumption Engine Map For Myvi Engine Volumetrically - Lim, Zhi Wey (Universiti Sains Malaysia, 2017)
This study generates fuel consumption engine maps of a Myvi engine (Daihatsu K3-VE). The objective of this study is to produce reliable fuel consumption engine maps. Previously, fuel consumption engine maps were achieved by gravimetric method. In this experimental study, the maps were completed in volumetric method whereby the rate of fuel consumption was measured in milliliter per second (ml/s). Burettes and a digital stopwatch were used throughout the experiment to calculate the fuel consumption rate. The results from this experiment are compared to the previous results by using the correlation coefficient in Matlab. The correlation coefficient for fuel consumption, brake power and brake thermal efficiency between gravimetric and volumetric experiments are less than 0.7, that indicates a moderate matching between both experiment results.